The effect of assertiveness-based empowerment on professional commitment and moral courage of nurses working in Shahrekord educational hospitals - Azadeh Nouroozi; Shahram Etemadifar; Fatemeh Deris; Shirmohammad Davoodvand (Shahrekord University of Medical Sciences, 2023)
Background and aims: Professional commitment and moral courage affect the quality of nursing care. Assertiveness is a necessary communication skill for nurses. The studies have less focused on the relationship between the mentioned variables. Therefore, this study examined the impact of assertiveness-based empowerment on professional commitment and moral courage. Methods: This quasi-experimental study was conducted on 70 nurses of Shahrekord educational hospitals who entered the study via available sampling and random allocation in intervention and control groups in 2021. Then, the assertiveness-based program was implemented in six 2-hour sessions for the intervention group. In both groups, data were collected before, immediately, and three months after the intervention using the Nurses' Professional Commitment Standard questionnaire (NPCS) and Sekerka's moral courage. The data was analyzed using SPSS software version 18. One sample t-test, chi-square, and repeated measurements analysis were used. Results: Before the study, neither group showed significant differences in demographic data, professional commitment, and moral courage (P>0.05). However, this difference was significant immediately after the intervention and three months later (P<0.001). Conclusion: The empowerment program based on assertiveness improved nurses' professional commitment and moral courage. Therefore, it is appropriate to use these moral virtues in the professional training of nurses to provide high-quality care to patients.